Protocol for the Evaluation of a Quality-Based Pay for Performance Scheme in Liberia - Bawo, Luke (BioMed Central, 2015)
Improving the quality of care at hospitals is a key next step in rebuilding Liberia’s health system. In order to improve the efficiency, effectiveness, and quality of care at the secondary hospital level, the country is developing a system to upgrade health worker skills and competencies, and shifting towards improved provider accountability for results, including a Graduate Medical Residency Program (GMRP) and provider accountability for improvements in quality through performance-based financing (PBF) at the hospital level.